Yeast glucan particles enable intracellular protein delivery in Drosophila without compromising the immune system - Bajgar, Adam; Saloň, Ivan; Krejčová, Gabriela; DoleŽal, Tomáš; Jindra, Marek; Štěpánek, František (Biomaterials science, 2019)
Glucan particles derived from yeast have been recently proposed as potential drug delivery carriers. Here, we demonstrate the potential of glucan particles for protein delivery in vivo, using the insect Drosophila melanogaster as a model organism. By employing genetic tools, we demonstrate the capacity of yeast glucan particles to spread efficiently through the Drosophila body, to enter macrophages and to deliver an active transcription factor protein successfully. Moreover, the glucan particles were nontoxic and induced only minimal immune response. The injection of glucan particles did not impair the ability of Drosophila to fight and survive infection by pathogenic bacteria. From this study, Drosophila emerges as an excellent model to test and develop drug delivery systems based on glucan particles, specifically aimed to regulate macrophages.
Keywords: glukany; proteiny Drosophily; Drosophila melanogaster; Drug Delivery Systems; lékové transportní systémy; nosiče léků; zvířata; makrofágy; kvasinky; Glucans; Yeasts; Animals; transkripční faktory; Drug Carriers; Drosophila Proteins; Macrophages; Transcription Factors